2003
DOI: 10.1088/0953-8984/16/2/020
|View full text |Cite
|
Sign up to set email alerts
|

Surface resistance and field emission current measurements on chemically vapour deposited polycrystalline diamond measured by scanning probe methods

Abstract: Scanning tunnelling microscopy (STM) and current imaging tunnelling current spectroscopy (CITS) methods were performed on polycrystalline diamond films grown on silicon substrates grown by microwave plasma-enhanced chemical vapour deposition. Large tunnelling currents were observed at some grain boundaries and crystal surfaces with secondary grains. Following atomic force microscopy (AFM) measurements, we performed scanning probe contact current (SPCC) measurements to investigate the spatial variation of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Accumulation of positive charge at the upper layer of the emitting sample may slow down the secondary electrons or even prevent their escape to the vacuum. It has been experimentally shown, that the more conductive diamond films exhibit also a much better electron emission properties [2,26,27]. The conductivity may be enhanced by doping or by increase of sp 2 conductive phase percent and grain boundary density.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of positive charge at the upper layer of the emitting sample may slow down the secondary electrons or even prevent their escape to the vacuum. It has been experimentally shown, that the more conductive diamond films exhibit also a much better electron emission properties [2,26,27]. The conductivity may be enhanced by doping or by increase of sp 2 conductive phase percent and grain boundary density.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown experimentally, that the more conductive diamond films also show much better electron emission properties. [97][98][99] The conductivity may be enhanced by doping or by increasing the percentage of the sp 2 conductive phase and grain boundary density. Since the studied diamond films are undoped, conductive paths extending to the surface are required to reduce the surface positive charge.…”
Section: Enhancement Of Electron Emission Frommentioning
confidence: 99%
“…It has been reported that BDD films with higher electrical conductivity exhibit a lower turn-on voltage for field emission. 15,17 The electron emission was observed to occur from sites of high electrical conductivity. The possibility of some channel and/or grain boundary conduction was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of some channel and/or grain boundary conduction was proposed. 15,17 Developing an understanding of how the electrochemical reaction rate might vary across the diamond electrode requires that one be able to characterize and spatially distinguish the physical, chemical, and electrical properties. Without question, polycrystalline diamond is one of the more structurally complex carbon electrodes with factors such as the boron-doping level, hydrogen content, grain boundary density, and electric double layer structure affecting electron-transfer rates.…”
Section: Introductionmentioning
confidence: 99%